What Drives BPRS Efficiency? A Study Of Financial Inclusion, Bank Characteristics, And Macroeconomic Factors - Akasumbawa, Muhammad Dedat Dingkoroci; Rukmana, Laelani; Razali; Andi Mardika (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
Islamic Rural Banks (BPRS) in Indonesia face persistent challenges in achieving optimal operational efficiency, which is crucial for their sustainability and ability to serve the unbanked population. However, the factors driving this efficiency remain underexplored, especially in relation to financial inclusion, internal bank characteristics, and macroeconomic dynamics. This study aims to examine whether financial inclusion, bank-specific factors (capital adequacy ratio, profitability, and default risk), and macroeconomic variables (inflation and exchange rate) influence the operational efficiency of BPRS, as measured by the Operating Efficiency Ratio (OER). Utilizing time series data from January 2014 to June 2024 and applying the ARDL approach, the results reveal that only the exchange rate (in the short term) and capital adequacy ratio (in the long term) significantly affect efficiency. In contrast, financial inclusion, profitability, default risk, and inflation do not show a statistically significant impact in either time frame. Practically, these findings indicate that BPRS managers should prioritize strengthening internal capital structures and managing exposure to exchange rate fluctuations, rather than relying solely on expanding financial inclusion or profitability improvements to enhance efficiency. Theoretically, the results highlight the limited role of financial inclusion in directly boosting operational performance without sufficient institutional readiness, and underscore the